ENHANCING LEARNING: EFFECTIVE STRATEGIES FOR TEACHING CHILDREN - Anora Abduraimova (Modern American Journals, 2025)
This topic is about most effective way of teaching children. How they can communicate to each other without embarrassment, how they can speak fluently and clearly. What is the best way to teach them? You can take answer to all your question.
Keywords: Visual aids, Learning style, Clear communication, Engagement, Interactive activities, Collaborative Learning, Flexibilty and Adabtabilty